Experimental Models of Metabolic Syndrome (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
In recent years, the prevalence of metabolic syndrome (MS) in modern society has been increasing, which leads to an increase in morbidity and mortality. The use of experimental models allows us to understand the causes of the development and progression of MS and to study potential methods of its prevention and treatment. MS is a multifactorial complex of pathological changes, and the choice of an adequate experimental model is fundamental in studying this condition. This review discusses the most common genetic models used to study MS, as well as methods for modeling this syndrome through external influences.